Pendampingan Pengajuan Sertifikasi Halal Produk Minuman Herbal Instan - Ratih Yuniastri; Ismawati Ismawati; Rika Diananing Putri; Imam Hanafi; Nur Fadhilah Syahrawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
One manifestation of the existence of small and medium enterprises (MSMEs) is a home industry which is currently growing rapidly and is a solution to improving people’s living standards. This industry can be relied upon to highlight regional local wisdom, especially Sumenep. One of the small and medium industries in Sumenep, namely KTH Bukit Lestari, located in the village of East Gadu, Ganding district, whose product is an instant herbal drink. This product has been marketed to several areas in East Java, but does not yet have halal certification. The team collaborated with the Sumenep Regional Forestry Service Branch through community service activities to assist KTH Bukit Lestari as a partner in submitting product certification. The training in the form of providing material on the urgency of halal certification an accompanying the completeness of submission documents has been carried out by the team and enthusiastically participated by partners. Partners actively participate during the activity and obtain halal certification for their products with the number ID35110000374340622.